A pan‐tumor review of the role of poly(adenosine diphosphate ribose) polymerase inhibitors - Chadi Hage Chehade; Georges Gebrael; Nicolas Sayegh; Zeynep Irem Ozay; Arshit Narang; Tony Crispino; Talia Golan; Jennifer K. Litton; Umang Swami; Kathleen N. Moore; Neeraj Agarwal (CA: A Cancer Journal for Clinicians, 2025)
Abstract Poly(adenosine diphosphate ribose) polymerase (PARP) inhibitors, such as olaparib, talazoparib, rucaparib, and niraparib, comprise a therapeutic class that targets PARP proteins involved in DNA repair. Cancer cells with homologous recombination repair defects, particularly BRCA alterations, display enhanced sensitivity to these agents because of synthetic lethality induced by PARP inhibitors. These agents have significantly improved survival outcomes across various malignancies, initially gaining regulatory approval in ovarian cancer and subsequently in breast, pancreatic, and prostate cancers in different indications. This review offers a comprehensive clinical overview of PARP inhibitor approvals, emphasizing their efficacy across different cancers based on landmark phase 3 clinical trials.